Réponses

2013-12-31T00:37:13+01:00
Bonsoir,

a) (7x + 4)(5 + 6x) + (9 - 2x)(8x - 3) = 35x + 42x² + 20 + 24x + 72x - 27 - 16x^2 + 6x
                                                        = 26x² + 137x -7

b) (4x - 3)(2 - 5x) - (9x + 7)(6 - x) = (8x - 20x² - 6 + 15x) - (54x - 9x² + 42 - 7x)
                                                    = 8x - 20x² - 6 + 15x - 54x + 9x² - 42 + 7x
                                                    = -11x² - 24x - 48
2013-12-31T00:57:07+01:00
A = (7x + 4)(5 + 6x) + (9 - 2x)(8x - 2)
a = (35x + 42x² + 20 +24x) +( 72x -16x² -18 +4x)
a = (42x² + 59x + 20) + (-16x² +76x -18)
a = 26x² +135x +2

b = (4x - 3)(2 -5x) - (9x +7)(6 - x)
b = (8x -20x² -6 +15x) - (54x - 9x² +42 -7x)
b = (-20x² +23x -6) - (-9x² +47x +42)
b = -20x² + 23x -6 +9x² -47x -42
b = -11x² -24x -48